2017
DOI: 10.4103/1119-3077.180073
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the enamel caries which were treated with casein phosphopeptide-amorphous calcium fluoride phosphate

Abstract: CPP-ACFP can be used in the treatment of white spot lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
2
16
0
1
Order By: Relevance
“…In this study, remineralization activity of the CPP‐ACFP group was found to be significantly higher in all time periods than the control group, which corroborates findings of previous studies (Hamba, Nikaido, Inoue, Sadr, & Tagami, ; Mehta et al, ; Yazicioğlu, Yaman, Güler, & Koray, ). This is because CPP‐ACFP exhibits superior remineralization properties to conventional fluoride varnishes (Ekambaram et al, ; Naveena, Nagarathana, & Sakunthala, ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, remineralization activity of the CPP‐ACFP group was found to be significantly higher in all time periods than the control group, which corroborates findings of previous studies (Hamba, Nikaido, Inoue, Sadr, & Tagami, ; Mehta et al, ; Yazicioğlu, Yaman, Güler, & Koray, ). This is because CPP‐ACFP exhibits superior remineralization properties to conventional fluoride varnishes (Ekambaram et al, ; Naveena, Nagarathana, & Sakunthala, ).…”
Section: Discussionsupporting
confidence: 92%
“…Dental caries is one of the major dental challenging problems maybe more prominent than other infectious diseases such as hypertension and heart infections. (1) It is easily detectable and reversible at an early stage. Once the incipient lesion proceeds to cavitation, the condition becomes irreversible.…”
Section: Introductionmentioning
confidence: 99%
“…(10) Diagnodent is a laser device measures uorescence, early demineralization with good to excellent sensitivity and improves the demonstrative precision of location of non-cavitated carious lesions. (1) This study will use Diagnodent to evaluate the impact of two remineralizing agents containing casein phosphopeptide amorphous calcium phosphate (CPP ACP), and Tricalcium phosphate (TCP) on white spot lesions.…”
Section: Introductionmentioning
confidence: 99%
“…These include dentifrices, chewing gums and topical pastes [10]. Bioactive agents based on milk proteincasein * email: murariu_alice@yahoo.com phosphopeptide (CPP) with amorphous calcium phosphate (ACP) have been also developed to release elements that enhance remineralization of the enamel and dentin [11]. CPP-ACP, a milk-derivative, comprises peptide fragments that are rich in phosphorylated seryl and glutamic acid residues that bind to amorphous calcium phosphate nanoparticles.…”
mentioning
confidence: 99%
“…These CPP-ACP nanoclusters are reported to adhere to enamel, plaque and pellicle, to inhibit bacterial adhesion to the tooth, and to act as a pH buffer against acid assault [10,12].When CPP ACP is combined with fluoride, the fluoride ions react with CPP ACP to form CPP amorphous calcium fluoride phosphate (ACFP). The CPP ACFPnanocomplex provides calcium, phosphate and fluoride ions to the surface of the teeth and therefore has an important effect on enamel remineralization [11].…”
mentioning
confidence: 99%